TAMI-79. THERAPEUTIC REVERSAL OF PRENATAL PONTINE ID1 SIGNALING IN DIPG. (12th November 2021) - Yadav, Viveka Nand; Harris, Micah K; Messinger, Dana; Thomas, Chase; Cummings, Jessica R; Yang, Tao; Woo, Rinette; Siddaway, Robert; Burkert, Martin; Stallard, Stefanie; Qin, Tingting; Mullan, Brendan; et al.
Abstract: Diffuse intrinsic pontine glioma (DIPG) is a highly aggressive pediatric brain tumor with rare survival beyond two years. This poor prognosis is largely due to the tumor's highly infiltrative and invasive nature. Nearly 80% of DMGs harbor K27M mutation in the genes encoding histone H3.1 ( H3F3A ) or H3.3 ( HISTIH3B ), often with concurrent ACVR1 mutation. Inhibitor of DNA-binding (ID) proteins are key transcriptional regulators of genes involved in lineage commitment and are associated with invasiveness and poor clinical outcomes in multiple human cancers. Introduction of H3K27M and ACVR1 mutations increase ID1 expression in cultured astrocytes, but this has not been confirmed in human tumors or targeted therapeutically. We developed an in-utero electroporation (IUE) murine H3K27M-driven tumor model, which demonstrates increased ID1 expression in H3K27M- and ACVR1 -mutated tumor cells. Exome and transcriptome sequencing analysis of multi-focal DMG tumors (n=52) and normal brain tissue revealed that increased ID1 expression is associated with H3K27M/ ACVR1 -mutation and brainstem location, and correlates with poor survival in patients. ChIP-sequencing for H3K27ac and H3K27me3 in multiple DMG tumors (n=5) revealed that the ID1 gene is epigenetically active, which matches the epigenetic state of murine prenatal hindbrain cells. Higher ID1-expressing astrocyte-like DIPG cells share a similar transcriptional program with ID1 + /SPARCL1 + positive oligo/astrocyte-precursor (OAPC) cells from the developing human brain and demonstrate upregulation of gene sets involved in regulation of cell migration. Both genetic and pharmacologic [cannabidiol (CBD)] suppression of ID1 result in decreased DIPG cell invasion/migration in vitro and invasion/tumor growth in multiple in vivo models. Mechanistically, CBD reduces proliferation through production of reactive oxygen species. Further, DIPG patients treated off-trial with CBD (n=15) displayed reduced ID1 tumor expression and improved overall survival. In summary, ID1 is upregulated in DIPG through K27M-mediated epigenetic reactivation of a developmental OAPC-like transcriptional state, and ID1-driven invasiveness of DIPG is therapeutically targetable with CBD.